2021
DOI: 10.1371/journal.pone.0260084
|View full text |Cite
|
Sign up to set email alerts
|

Men and infertility in The Gambia: Limited biomedical knowledge and awareness discourage male involvement and exacerbate gender-based impacts of infertility

Abstract: Introduction Infertility in Sub-Saharan Africa constitutes an important social and public health problem. Yet, there is a paucity of research on the experiences of men living with infertility, especially in West Africa. This study explored men’s aetiological knowledge, views and experiences of infertility in the West Coast region of The Gambia, West Africa. Methodology An explorative qualitative study was conducted among men living in the rural and urban communities of the West Coast region of The Gambia usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…This is further confirmed in this study, which indicate that male partners are more involved in infertility treatment in follow-up visits compared to initial visits. These findings also illustrate similarity with a studies conducted in SSA [ 34 , 49 , 50 ]. Surprisingly, in our study, less than 25% of the consultations are reportedly for male factor infertility, as many studies [ 51 – 54 ] conducted elsewhere have found that the causes of infertility are equally split between genders (in heterosexual couples).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is further confirmed in this study, which indicate that male partners are more involved in infertility treatment in follow-up visits compared to initial visits. These findings also illustrate similarity with a studies conducted in SSA [ 34 , 49 , 50 ]. Surprisingly, in our study, less than 25% of the consultations are reportedly for male factor infertility, as many studies [ 51 – 54 ] conducted elsewhere have found that the causes of infertility are equally split between genders (in heterosexual couples).…”
Section: Discussionsupporting
confidence: 90%
“…Given that the majority of institutions reported most of the consultation were attended by women and the members of the couple visit the facility alone, we can conclude that women attend initial consultations for infertility without their partner [ 48 ]. Although in approximately half of initial consultations by women for fertility problems their partner was not present (results are comparable in both health sectors), the preference of the medical practitioners is to manage infertility as a couple’s issue [ 34 ]. This is further confirmed in this study, which indicate that male partners are more involved in infertility treatment in follow-up visits compared to initial visits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that about 48 million couples and 186 million individuals suffer from infertility [2,3]. Although infertility is not a life-threatening condition, it is often associated with emotional, physical, psychological distress, social and socioeconomic factors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%